Mode-Locking of All-Fiber Lasers Operating at Both Anomalous and Normal Dispersion Regimes in the C- and L-Bands Using Thin Film of 2D Perovskite Crystallites - Hong, Seongjin; Lédée, Ferdinand; Park, Jaedeok; Song, Sanggwon; Lee, Hyeonwoo; Lee, Yong Soo; Kim, Byungjoo; Yeom, Dong Il; Deleporte, Emmanuelle; Oh, Kyunghwan (Laser and Photonics Reviews, 2018)
Two-dimensional hybrid organic–inorganic perovskites have recently attracted attention in various optoelectronic applications. A novel thin film of 2D perovskite (C6H5C2H4NH3)2PbI4 crystallites is synthesized and its nonlinear optical properties are experimentally investigated within the optical gain of an Erbium-doped fiber. Utilizing its unique nonlinear optical response, efficient mode-locking of an all-fiber Erbium laser is demonstrated at the anomalous dispersion regime in both the C- and L-bands stably generating femtosecond pulse trains, where the thin film of 2D perovskite crystallites function as an in-line saturable absorber. At this anomalous dispersion regime, self-started femtosecond pulses are generated whose center wavelength are tuned from 1565.9 nm in C-band and 1604 nm in L-band by adjusting the optical gain. Furthermore, by managing the chromatic dispersion of the total fiber laser cavity to reach the normal dispersion regime, a stable dissipative soliton is successfully generated in the C-band with the spectral bandwidth of 15 nm and pulse duration of 3.2 ps. Detailed material properties of the thin film of 2D perovskite crystallites, their characterization, and fiber laser mode-locking performance is reported.
Keywords: All-fiber Erbium lasers; Anomalous dispersion; Dissipative solitons; Erbium doped fibers; Non-linear optical properties; Nonlinear optical response; Optoelectronic applications; Spectral bandwidth; 2D perovskites; mode-locking lasers; optical fiber lasers; perovskites; ultrafast lasers